Effects of Different Irrigation Regimes and Genotypes on Yield Contributing Parameters of Potato (Solanum Tuberosum L.) Under Chhattisgarh, India (Bangladesh Journal of Botany, 2023)
The field experiment was conducted at the Horticultural Research Farm, College of Agriculture, Indira Gandhi Krishi Vishwavidyalaya, Raipur, Chhattisgarh, India during Rabi 2018-19 in Split plot Design with four level of irrigation regimes and four potato genotypes. The irrigation treatments were allotted in the main plot while, potato genotypes allotted in the sub-plots. At 75 days after planting (DAP) and 90 days after planting (DAP), the various yield contributing parameters were affected significantly by the different irrigation regimes except the plant emergence and number of shoots/plant. The number of shoots/plant, number of total leaves/plant, fresh weight of tubers/plant (g), total number of tuber/plant and harvest index (%) were significantly affected by the different irrigation regimes and potato genotypes. The plant with irrigation at 25 mm cumulative pan evaporation (CPE) produced the maximum plant height, number of shoots/plant, number of total leaves/plant, number of tubers/plant, fresh weight/plant and harvest index at 75 DAP and 90 DAP, respectively. The potato genotype AICRP-P-38 gave the highest fresh weight of tuber/ plant, number of tubers/plant and harvest index at 75 DAP and 90 DAP, respectively.Bangladesh J. Bot. 52(1): 211-216, 2023 (March)